Introduction of local coordinates for a countable system of differential equations in the neighborhood of an invariant manifold - Zahlivnaya, О. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We establish conditions of the existence of local coordinates for a countable system of differential equations in the neighborhood of an invariant manifold and present the form of this system in these coordinates.